Sistem Informasi Rekomendasi Kartu Indonesia Pintar (KIP) Kuliah Gerakan Ayo Kuliah (GAK) dengan User Acceptance Testing (UAT) - Salsabilla Qurrota A'yuni; Irwan Adi Pribadi; Ridho Sholehurrohman; Dwi Sakethi (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
Information systems play a crucial role in enhancing the performance of an organization. One of the programs aiming to assist students, particularly those who are beneficiaries of the Program Keluarga Harapan (PKH) and need a recommendation letter for the Kartu Indonesia Pintar (KIP) scholarship from the Governor of Lampung, is known as Gerakan Ayo Kuliah (GAK). GAK also serves as a platform to encourage and generate interest in pursuing higher education among high school students from various districts across Lampung Province. However, the absence of a digital system for introducing and collecting data about the Gerakan Ayo Kuliah program has resulted in decreased enthusiasm among participants, and the program's reach remains limited. Additionally, the selection process for program participation is not as efficient as it could be. This research focuses on the development of an information system to manage KIP recommendation letters for college students who receive assistance from the GAK Social Service of Lampung Province. The system was constructed using the Waterfall methodology and was programmed using PHP, utilizing the Codeigniter framework. The system's functionality was evaluated through User Acceptance Testing. As a result, this research has produced a system that facilitates the connection between applicants, namely students, and the Gerakan Ayo Kuliah program when it comes to selecting recommendation letter data.